Pengaruh Motivasi Kerja dan Disiplin Kerja Terhadap Kinerja Karyawan: Literature Review - Riyanto; Rokhim Sunandi; Dini Nur Alpiah (JURNAL ILMIAH RESEARCH STUDENT, 2024)
Every employee must have experienced boredom in facing the work routine every day. Monotonous routines can reduce the spirit and motivation of work that is owned so that later it will have a bad impact on company performance. Giving work motivation to an employee appropriately will create enthusiasm, and encouragement at work so that this will increase work productivity. To achieve company goals, potential human resource management will affect employee performance which in turn will affect company performance. To be able to show performance, companies are required to uphold the motivation and work discipline of employees. This study aims to determine the effect of work motivation and work discipline on employee performance. The literature review research method was carried out using the PICO search on the Google Scholar database . There are 5 journals that meet the criteria and show the results that the t-count value is greater than the t-table and the significant value is smaller than the alpha value (0.05). Then hypothesis one (H1) and hypothesis two (H2) in this study are accepted. This shows that the better the employee discipline, the better the performance will be. So that the influence of work motivation and work discipline on employee performance is because the strategy implemented by the company can be pursued. The results of regression analysis show that work motivation and work discipline have a positive effect on employee performance.